Teenage Patients with Class II Subdivision Treated with Aligners and Elastics: A Retrospective Study - Vincenzo Quinzi; Andrea Conigliaro; Eda Fani; Lucia Memè; Fabiana Fiasca; Nicolò Carugo; Giuseppe Marzo (Medicina)
Background and Objectives: This study aimed to evaluate the outcomes of Class II subdivision teenage patients treated with Invisalign® clear aligners (CAs) and elastics. Materials and Methods: A total of 23 individuals aged 14.3 ± 2.5 years were enrolled in this study. The participants were divided into Group 1 (mandibular midline deviation) and Group 2 (maxillary midline deviation). The midline deviation from the facial midline; anteroposterior discrepancy; overjet (OJ), overbite (OB), and Peer Assessment Rating (PAR) scores; upper incisor and lower incisor (L1) positions; and angulation were measured at the beginning (T0) and end (T1) of the orthodontic treatment. Results: Group 1 showed significant higher variations in OJ (−2.3 ± 2.3 vs. −0.6 ± 0.8, p < 0.001), OB (−2.1 ± 2.3 vs. −1.1 ± 1.4, p < 0.001), PAR score (−32.0 ± 11.7 vs. −27.3 ± 13.1, p < 0.001), L1-to-mandibular-plane angle (−3.6 ± 7.0 vs. −1.3 ± 3.2, p < 0.001), and interincisal angle (10.07 ± 8.7 vs. 5.9 ± 5.3, p = 0.007). The midline deviation was the only measurement with higher variation in Group 2. The average distance between the mesiobuccal cusp of the maxillary first molar and the buccal groove of the mandibular first molar was 0.3 ± 0.5 mm. Conclusions: A total of 21 patients achieved bilateral Class I (91% success rate) and demonstrated great improvement (72–96%) in PAR scores. Regardless of the etiology of malocclusion, the orthodontic correction of the Class II subdivision with CAs showed high accuracy and predictable results.